2016
DOI: 10.1186/s40064-016-3650-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bowel resection margins in node negative colon cancer

Abstract: PurposeSurgical intestinal resection margins in colon cancer are a longstanding debate in terms the optimal distance between the tumor and the colonic section line. The aim of this study is to define the oncological outcomes in relation to surgical margins, measured in terms or recurrence rate, time-to-recurrence, disease-free survival and overall survival in a population of node negative colon cancer patients.MethodsWe conducted a retrospective observational longitudinal single institution study. All patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…It has also been suggested that metastatic lymph nodes may be found approximately 8 to 10 cm of the colonic segment around the tumor, and hence the removal of the distal and proximal surgical margin with a 5 cm safety margin is recommended (17). In our study, median length of the proximal margin was found to be 10 cm, while mean distal margin length was 6.5 cm.…”
Section: Discussionsupporting
confidence: 48%
“…It has also been suggested that metastatic lymph nodes may be found approximately 8 to 10 cm of the colonic segment around the tumor, and hence the removal of the distal and proximal surgical margin with a 5 cm safety margin is recommended (17). In our study, median length of the proximal margin was found to be 10 cm, while mean distal margin length was 6.5 cm.…”
Section: Discussionsupporting
confidence: 48%
“…Furthermore, Rocha et al identify that location of tumor also correlates with margin status, with sigmoid resections more likely to have shorter margins and fewer lymph nodes retrieved, with lymphatic involvement as a significant risk factor for recurrence. 12 With regard to coordination of care in the emergent setting, our analysis suggests that emergent cases are provided equivalent initiation of oncology care for those with advanced disease (margin positive, node positive, metastatic, or other high-risk patients such as elevated CEA and poorly differentiated tumor). 13 While it was initially thought that emergent cases would be at a disadvantage in terms of oncology care due to new diagnosis and less case volume for referrals, the data analysis suggests an equivalent coordination of care for all colon resections at our institution.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Rocha et al identify that location of tumor also correlates with margin status, with sigmoid resections more likely to have shorter margins and fewer lymph nodes retrieved, with lymphatic involvement as a significant risk factor for recurrence. 12…”
Section: Discussionmentioning
confidence: 99%
“…As far as our patient was concerned, we performed an intraoperative frozen section, confirming tumor-free margins of 5 cm [ 14 ]. We then restored the ascending-transverse intussusception and performed an extended right hemicolectomy with ileocolic anastomosis.…”
Section: Discussionmentioning
confidence: 99%